Predominant role of Haemophilus influenzae in the association of conjunctivitis, acute otitis media and acute bacterial paranasal sinusitis in children - Yali Hu; Ping‐Ing Lee; Po‐Ren Hsueh; Chun‐Yi Lu; Luan‐Yin Chang; Li‐Min Huang; Tu‐Hsuan Chang; Jong‐Min Chen (2021)
Abstract Haemophilus influenzae is a predominant pathogen for conjunctivitis, acute otitis media and acute bacterial paranasal sinusitis in children. We undertook this study to investigate the possible association among these diseases. Children younger than 18-year-old with a diagnosis of bacterial conjunctivitis plus acute otitis media and/or acute bacterial paranasal sinusitis during 2009–2018 were included. Sampling for bacterial cultures was obtained from the lower palpebral conjunctiva and/or ear discharge with cotton-tipped swabs. A total of 67 children were recruited and the age was 29.5 (± 22.4) months in average. Fifty-seven children had conjunctivitis–otitis media syndrome and eight of them had a concurrent diagnosis of acute paranasal sinusitis. Ten children had conjunctivitis and acute paranasal sinusitis simultaneously. Clusters in household were observed in 50.7% children. Most common isolates were Haemophilus influenzae (70%), Moraxella catarrhalis (18%), and Staphylococcus aureus (8%). Antibiotic resistance rate of H. influenzae was 80% for ampicillin, 18% for amoxicillin–clavulanate, and 11% for the second or third-generation cephalosporins. Apart from well-known conjunctivitis–otitis media syndrome, acute paranasal sinusitis may also be linked to conjunctivitis with a similar pathogenic process. Simultaneous presence of these infections may guide the choice of empiric antibiotics toward H. influenzae .